Práticas de contagem no contexto de lendas: manifestações orais de crianças de cinco anos em atividades orientadoras de ensino - Jacomelli, Cristiane Vinholes (2013)
This work studies the oral manifestations of five years old children in activities of counting practice, where they are exposed to problem-situation involving the conceptual nexus of numbers in the legends context. The methodology is based in a qualitative perspective, specifically in one case study in which the peculiar case is a group of children of five years old inserted in a non-formal space of learning, that seeks to work toward a historical-cultural perspective. The analysis is based on an interpretative vision, the expressed manifestation of the children during four teaching activities. The manifestations have been divided in three units of significance where we present the episodes that represent the children dialog during the activities, transcribed from video-graphic records. Through the analysis of the children speech it became evident that some of them have used the conceptual nexus of numbers to answer to the proposed situations. The children also showed some influence of the school practices while answering the activities, given the difficulty of using diversified practice of counting. Ultimately, it was perceived that many times the children worried more about the legends and that they forgot the mathematical problems addressed in the activities. We realized that the Teaching Guiding Activity can be a fertile terrain to develop mathematical concepts with children in elementary school education.